Age of surveillance capitalism : the fight for a human future at the new frontier of power - Zuboff, Shoshana (London, 2019)
The challenges to humanity posed by the digital future, the first detailed examination of the unprecedented form of power called "surveillance capitalism," and the quest by powerful corporations to predict and control us. The heady optimism of the Internet's early days is gone. Technologies that were meant to liberate us have deepened inequality and stoked divisions. Tech companies gather our information online and sell it to the highest bidder, whether government or retailer. Profits now depend not only on predicting our behaviour but modifying it too. How will this fusion of capitalism and the digital shape our values and define our future. Shoshana Zuboff shows that we are at a crossroads. We still have the power to decide what kind of world we want to live in, and what we decide now will shape the rest of the century. Our choices: allow technology to enrich the few and impoverish the many, or harness it and distribute its benefits. The Age of Surveillance Capitalism is a deeply-reasoned examination of the threat of unprecedented power free from democratic oversight. As it explores this new capitalism's impact on society, politics, business, and technology, it exposes the struggles that will decide both the next chapter of capitalism and the meaning of information civilization. Most critically, it shows how we can protect ourselves and our communities and ensure we are the masters of the digital rather than its slaves.